Nanoengineered Bioinks: Printing Therapeutic Proteins in 3D using Nanoengineered Bioink to Control and Direct Cell Migration (Adv. Healthcare Mater. 11/2019). Issue 11 (6th June 2019) - Peak, Charles W.; Singh, Kanwar Abhay; Adlouni, Mu'ath; Chen, Jeffrey; Gaharwar, Akhilesh K.
Abstract : In article number1801553 by Charles W. Peak, Akhilesh K. Gaharwar, and co‐workers, a nanoengineered bioink loaded with therapeutic proteins is designed to direct cell function in a 3D printed construct. This approach to design biologically active inks to control and direct cell migration can be used to engineer 3D vascularized tissue structure for regenerative medicine.